Thermal Diffusivity of Glass Ceramic Synthesized from Soda Lime and Coal Fly Ash - Edros, Norfarezah Hanim (2010)
Glass ceramics are polycrystalline materials of fine microstructure that are produced by the controlled crystallization of a glass. The previous review of other researchers revealed that knowledge and expertise has been accumulated on the process of transformation of silicate waste into useful glass ceramic products. The aim of this research is to study the thermal diffusivity of a glass ceramic made from a mixture of soda lime silica and coal fly ash. The effect of sample compression pressure, sintering temperature and sample composition on the thermal diffusivity value was investigated in detail. All samples were measured using the Laser Flash Apparatus (LFA), X-Ray Fluorescence (XRF), Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). It was found that the thermal diffusivity value of the samples is dependent on the pressure, sintering temperature and sample composition. Higher sintering temperature, coal fly ash content and compression pressure resulted in higher thermal diffusivity value. The experimental results showed that the thermal diffusivity value is in the range of 0.102 mm2/s to 0.858 mm2/s. As the ambient temperature increased from room temperature up to 300°C, the thermal diffusivity values were also increased. This suggests that thermal diffusivity is basically influenced by phonon interaction that determines the phonon mean free path. The density value and linear shrinkage increase as the coal fly ash content and sintering temperature increased. XRD results revealed the formation of Diopside (CaMgO6Si2) and Wollastonite (CaSiO3) phases.